Numerical study of forebody wake effect on axisymmetric parachute opening shock and drag reduction. Issue 2 (3rd March 2016) - Tang, Jianhua; Qian, Linfang
ABSTRACT: Parachute–forebody distance is a parameter which is amongst the most critical factors to be considered in forebody wake effect. In this study, a new axisymmetric parachute–forebody coupling model is developed. Axisymmetric wrinkling membrane element is built to assess the dynamic response of the parachute canopy membrane under fluid pressure. Besides, fluid model and its further implementation on the fluid structure analysis are discussed. With the proposed method, the wake effect on both the opening shock during inflation state and the drag reduction during steady state can be obtained efficiently. Finally, numerical model is validated with published experimental result and further employed to investigate the influence of distance parameters on fluid–parachute coupling behaviour. On the basis of numerical results, failure distance during the inflation process and critical forebody–parachute distance are determined. The results show that forebody–parachute distance has a strong influence on flow behaviour around the parachute in both inflation state and steady descent state.